PENGELOLAAN SUMBERDAYA PERIKANAN DALAM KERANGKA UNDANG-UNDANG OTONOMI DAERAH - Johan Erwin Isharyanto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
The fishery and marine sector is one of the sectors that is expected to contribute to the recovery efforts of the Indonesian economy. However, marine and fisherydevelopment as the main pillar of the national economy still requires the struggle and endless hard work of all its stakeholders. Regional autonomy requires the Region to participate and be responsible in the development process in its own region in the framework of realizing equitable development. This article concludes that Article 18 of Law no. 32 of 2004 became the basis of legal construction that designed the scenario of autonomous management of fishery resources in regions that have marine territory by giving authority to manage resources in marine areas. The lack of clarity on the regulation of autonomous authority over control of marine fisheries resources among regions has the potential to result in interpretations that are not in line with the law and the conflict between marine fishery resources between regions.